Role of Head Teachers in Sustaining Academic Continuity Amidst Smog in Southern Punjab, Pakistan - Khizer Hayat (Muslim Education Review, 2025)
Recently, smog has emerged as an environmental danger due to climate change to the lives of people in Punjab, Pakistan; it harms children’s health, causing breathing and lung diseases, disrupting school schedules, and results in study loss. This study explores the role of head teachers in sustaining academic continuity in government primary schools in southern Punjab during school closures caused by smog season. This qualitative research uses case study design to explore specific strategies head teachers employ to overcome the study loss. The study investigates how school leaders use their leadership qualities, proactive planning, and coordination to ensure the continuity of teaching and learning within their schools. We used semi-structured interviews with two school heads of public primary schools in southern Punjab. Documents’ analysis was also employed from the health Department Punjab, and The Punjab Environment Protection and Climate Change Department. The study found that head teachers can use leadership skills to handle educational crises posed by smog. The main recommendations are that school leaders can play a significant role in saving students’ valuable time by leveraging leadership skills and the effective use of technology and remote learning teaching methods, even in the absence of funding, so school leaders can make a huge difference with existing resources. The results suggest that relevant authorities should take serious policy measures to encourage and train school heads.